The Role of Islamic Religious Education Teachers in Internalizing the Value of Mutual Help between Grade VIII Students at SMPN 11 Baubau - Nurma, Nurma; Sulasri, Sulasri; Yahya, Safaruddin (Journal of English Language and Education, 2025)
This study aims to explore the role of Islamic Religious Education (IRE) teachers in internalizing the value of mutual assistance among eighth-grade students at SMPN 11 Baubau. Employing a qualitative approach, data were collected through observations, interviews, and document analysis. The findings indicate that IRE teachers play a crucial role as role models, integrators of values within the learning process, facilitators of collaborative activities, character mentors, and bridges between the school and parents. The internalization of mutual help values is supported by exemplary behavior, routine practices, family involvement, and the creation of a positive classroom environment. Despite these efforts, several challenges were identified, including variations in student character, limited time for values education, the influence of social media, and low initial awareness of mutual help values among students. Nevertheless, with consistent and collaborative strategies, the value of mutual assistance can be effectively instilled, shaping students into empathetic, responsible individuals with strong social solidarity.